2014
DOI: 10.4103/2249-4863.137611
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and practices of oral hygiene and its relation to sociodemographic factors among patients attending the general outpatient department in a tertiary care hospital of Kolkata, India

Abstract: Background:Periodontal diseases, dental caries, malocclusion, and oral cancer are the most prevalent dental diseases affecting people in the Indian community.Objective:The study was conducted to assess the awareness and practices on oral hygiene and its association with the sociodemographic factors among patients attending the general Outpatient Department (OPD).Materials and Methods:A cross-sectional study was conducted among 224 patients attending the general OPD of the SSKM Hospital, Kolkata, India, from 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
(15 reference statements)
2
14
1
3
Order By: Relevance
“…34 Third, people with low socioeconomic status also have low oral health literacy, which is associated with poor knowledge, attitudes and practices of oral hygiene. 35 Busby et al 36 showed that oral health generally tends to decline with age. We showed that oral hygiene status was poorer for older children.…”
Section: Discussionmentioning
confidence: 99%
“…34 Third, people with low socioeconomic status also have low oral health literacy, which is associated with poor knowledge, attitudes and practices of oral hygiene. 35 Busby et al 36 showed that oral health generally tends to decline with age. We showed that oral hygiene status was poorer for older children.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the study conducted in India. 16 In this study, findings revealed that dental floss was not used by 96% of participants, which is 5 5. How do you select your tooth brush and paste similar to the results of previous studies.…”
Section: Disscussionmentioning
confidence: 62%
“…While the findings of present study are almost similar to the previous studies conducted at home and abroad including India and Jordan. [12][13][14][15][16][17] In present study 68% of participants used to brush their teeth once a day. The result of present study is consistent with the results of previous studies.…”
Section: Disscussionmentioning
confidence: 98%
“…They could have migrated at a later age in life from rural areas of India. The use of salt with sea weed, neem stick, charcoal, toothpowder and brick powder using finger is still a prevalent oral hygiene practice in rural areas ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%